Modulation of Mitochondriotropic Properties of Cyanine Dyes by in Organello Copper‐Free Click Reaction. (31st July 2017) - Negwer, Inka; Hirsch, Markus; Kaloyanova, Stefka; Brown, Tom; Peneva, Kalina; Butt, Hans‐Jürgen; Koynov, Kaloian; Helm, Mark
Abstract: Cyanine (Cy) dyes show a general propensity to localize in polarized mitochondria. This mitochondriotropism was used to perform a copper‐free click reaction in the mitochondria of living cells. The in organello reaction of dyes Cy3 and Cy5 led to a product that was easily traceable by Förster resonance energy transfer (FRET). As determined by confocal laser scanning microscopy, the Cy3–Cy5 conjugate showed enhanced retention in mitochondria, relative to that of the starting compounds. This enhancement of a favorable property can be achieved by synthesis in organello, but not outside mitochondria. Abstract : Mitochondrial meeting point : Cyanine (Cy) dyes show a general propensity to localize in polarized mitochondria. This mitochondriotropism is used to perform a copper‐free click reaction in the mitochondria of living cells. A Cy3–Cy5 conjugate shows enhanced retention in mitochondria, compared with the starting compounds. This enhancement of a favorable property can be achieved by synthesis in organello, but not outside mitochondria.